2017
DOI: 10.5455/ijmsph.2017.0956717102016
|View full text |Cite
|
Sign up to set email alerts
|

A study of antibiotic sensitivity pattern of Pseudomonas aeruginosa isolated from a tertiary care hospital in South Chhattisgarh

Abstract: Background: Pseudomonas aeruginosa is one of the leading causes of hospital-acquired as well as community-acquired infections due to significant changes in microbial genetic ecology; as a result of indiscriminate use of antibiotics, the spread of multidrug resistance (MDR) is now a global problem. Its general resistance is due to a combination of factor. Several different epidemiological studies indicate that antibiotic resistance is increasing in clinical isolates. Objectives: The present study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
4
4
0
3
Order By: Relevance
“…Similar rate were observed by Javiya et al, (2008), 67.86%and Senthamarai et al, (2014, 65.38% and higher rates of resistance 75% were observed in Rajput et al, (2015). We found that 60% isolates were resistance to Aztreonam in our study, similar to other studies by Yadav et al, (2017), 63.7%. We found that 55.9% isolates were resistance to Gentamicin in our study, similar to other studies by Senthamarai et al, (2014), 51.92%.…”
Section: Chart1 Graphical Presentation Of Resistance (%) Towards Varsupporting
confidence: 82%
“…Similar rate were observed by Javiya et al, (2008), 67.86%and Senthamarai et al, (2014, 65.38% and higher rates of resistance 75% were observed in Rajput et al, (2015). We found that 60% isolates were resistance to Aztreonam in our study, similar to other studies by Yadav et al, (2017), 63.7%. We found that 55.9% isolates were resistance to Gentamicin in our study, similar to other studies by Senthamarai et al, (2014), 51.92%.…”
Section: Chart1 Graphical Presentation Of Resistance (%) Towards Varsupporting
confidence: 82%
“…Yurtdışında yapılan çalışmalarda piperasilin / tazobaktam için % 7-38.5, seftazidim için % 15.7-58.0, sefepim için % 14.6-52.5, imipenem için % 8.6-20.8, meropenem için % 6.2-6.5 ve aztreonam için % 36.3 direnç oranları bildirilmiştir (1,13,21,22,28) . ABD, Fransa, Almanya, İtalya ve İspanya'da yapılan ortak bir çalışmada sefalosporinlere karşı direnç oranı % 18.6-40.5, karbapenemlere karşı % 21-52.7 ve beta-laktamaz inhibitörlerine karşı % 55.8-79.5 gibi yüksek direnç oranları saptanmıştır (16) .…”
Section: Gereç Ve Yöntemunclassified
“…Pseudomonas tedavisinde kullanılan bir diğer grup antibiyotik kinolonlardır. Ülkemizde yapılan bazı çalışmalarda siprofloksasin için direnç oranı % 19.7-45.9, levofloksasin için % 23.8-52, yurtdışında yapılan çalışmalarda siprofloksasin için direnç oranı % 22.5-49 levofloksasin için % 16.5-26.7 olarak bildirilmiştir (1,2,4,6,9,11,12,15,(21)(22)(23)25,28,29) . Çalışmamızdaki kinolon grubu ilaçlara karşı son üç yılda direnç oranların-da herhangi bir değişiklik gözlenmemiş olup (p>0.05) siprofloksasin için saptadığımız % 27.4 ve levofloksasin için % 25.5'lik direnç oranı bu çalışmalardaki direnç oranlarıyla benzerlik göstermiştir.…”
Section: Gereç Ve Yöntemunclassified
See 1 more Smart Citation
“…With a rise in resistance to antimicrobials in the 21 st century, Pseudomonas aeruginosa has not been exempted from this public health problem. According to Yadov et al [17] advances in medical and surgical healthcare facilities with the introduction of antimicrobial agents having anti-Pseudomonal activities have not been able to avert or reduce life threatening infections caused by Pseudomonas aeruginosa nor their complications in hospital acquired infections [18]. From the time of Mayhall's [19] report on the complications resulting from hospital acquired infections due to Pseudomonas aeruginosa, this Gram negative bacterium belonging to the family Pseudomonadaceae has risen to become a challenging ISSN 0970-938X www.biomedres.info…”
Section: Introductionmentioning
confidence: 99%